How communist is North Korea?: From the birth to the death of Marxist ideas of human rights - SONG, Jiyoung (Institutional Knowledge at Singapore Management University, 2010)
This article focuses on the Marxist characteristics of North Korea in its interpretation of human rights. The author's main argument is that many Marxist features pre-existed in Korea. Complying with Marxist orthodoxy, North Korea is fundamentally hostile to the notion of human rights in capitalist society, which existed in the pre-modern Donghak (Eastern Learning) ideology. Rights are strictly contingent upon one's class status in North Korea. However, the peasants' rebellion in pre-modern Korea was based on class consciousness against the ruling class. The supremacy of collective interests sees individual claims for human rights as selfish egoism, which was prevalent in Confucian ethics. The prioritization of subsistence rights and material welfare over civil and political rights was also the foremost important duty of the benevolent Confucian king. Finally, unlike Marx's reluctant use of the language of ‘duties’, rights are the offspring of citizens' duties in North Korean human rights discourse.